Population size of Chamois – Rupicarpa rupicarpa (Linnaé) in Diva Grabovica mountain chain (VETERINARIA, 2020)
Field work research of the Chamois (Rupicarpa rupicarpa) in the Diva Grabovica mountain chain was conducted from January, 2007 until January, 2008. In this period, the research was conducted during all four seasons. In research, a relativecount method was used, based on the estimation of the number of the Chamois in the area. In the investigated area, about 30 specimens of the Chamois were assessed, 15 females (50,0%), 5 males (16,7%), and 10 juveniles (33,3 %). In addition to the counting, a visual analysis of the stools was performed rendering nutritional information about the Chamois. It was established that the food was mostly represented by all types of the mountain herbs and grass, and also the leaves, buds and green branches of the mountain trees. In the winter time, the Chamois also eat lichen, moss, bark, and different pine leaves.
Keywords: Chamois; male; female; juvenile; Diva Grabovica